2018
DOI: 10.3390/cells7070073
|View full text |Cite
|
Sign up to set email alerts
|

Animal Female Meiosis: The Challenges of Eliminating Centrosomes

Abstract: Sexual reproduction requires the generation of gametes, which are highly specialised for fertilisation. Female reproductive cells, oocytes, grow up to large sizes when they accumulate energy stocks and store proteins as well as mRNAs to enable rapid cell divisions after fertilisation. At the same time, metazoan oocytes eliminate their centrosomes, i.e., major microtubule-organizing centres (MTOCs), during or right after the long growth phases. Centrosome elimination poses two key questions: first, how can the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 136 publications
1
23
0
Order By: Relevance
“…In higher eukaryotes and plants, the bipolar spindle is formed independent of the centrosome through the pathway referred to as the acentrosomal pathway [99][100][101]. Historically, the acentrosomal pathway is extensively characterised in vitro using extracts prepared from Xenopus oocytes, where the Ran GTPase acts as a master regulator [102,103]. This pathway is functional in vivo in several cell types which are naturally devoid of centrosomes (eg.…”
Section: Force Generation In the Acentrosomal Cellsmentioning
confidence: 99%
“…In higher eukaryotes and plants, the bipolar spindle is formed independent of the centrosome through the pathway referred to as the acentrosomal pathway [99][100][101]. Historically, the acentrosomal pathway is extensively characterised in vitro using extracts prepared from Xenopus oocytes, where the Ran GTPase acts as a master regulator [102,103]. This pathway is functional in vivo in several cell types which are naturally devoid of centrosomes (eg.…”
Section: Force Generation In the Acentrosomal Cellsmentioning
confidence: 99%
“…The pathological effect of TEX12 on centrosome function in cancer cells raises the possibility that its physiological function during meiosis might also include a centrosome function, in addition to its well-established role in chromosome synapsis. While it is generally thought that centrosomes dissipate in gametogenesis, with the loss of centrioles and formation of asymmetric microtubule organising centres, recent studies have reported the retention of centriole remnants in mature oocytes [26][27][28][29][30] . In mice it has been extensively demonstrated that oocytes contribute the centrosomes while centrosomal proteins and centrioles was reported to come from the sperm 31 .…”
Section: Main Textmentioning
confidence: 99%
“…Boveri also first postulated that the first centrosome within a zygote originates from the fertilizing sperm cell, while the unfertilized egg lacks a centrosome [ 7 ]. This holds true for many animal species and is discussed in detail in the both the reviews of Avidor–Reiss and Gruss in this issue of Cells [ 10 , 11 ]. After these groundbreaking works of the late nineteenth century centrosome research became stuck in its descriptive character and poked along until the late 80s of the twentieth century with a relatively low number of key papers, despite the centrosome’s central importance for cellular function.…”
Section: Centrosome Research Retrospectivementioning
confidence: 99%
“…Here, the small GTPase Ran is rendered into its GTP form through the chromatin-associated GTP/GDP exchange factor Rcc1, which together with Aurora A activates several spindle assembly factors [ 52 , 53 , 54 , 55 ]. The latter organize γ-tubulin complexes to nucleate microtubules, which become arranged in a bipolar spindle through the activity of motor proteins including dynein, a bipolar Eg5-like kinesin and a chromokinesin [ 11 ]. Further examples for non-centrosomal microtubule organization also in interphase have been especially well-investigated in Drosophila .…”
Section: Evolution Of Centrosomal Structuresmentioning
confidence: 99%